Curso de capacitação para líderes, voluntários, profissionais e gestores de comunidades terapêuticas: o conhecimento em relação ao álcool, crack e outras drogas - Nunes, Aline Figueiredo [UNESP] (2015)
Introduction: This study investigated the difference in knowledge among students of the first online training program addressing alcohol, crack and other drugs for Therapeutic Community (TC) agents made available in Brazil (CapacitaCT), provided by the National Secretariat on Policies on Alcohol and Drugs (SENAD) in partnership with the Botucatu Medical School (FMB-UNESP). Objective: To describe (i) students' self-reported knowledge on issues related to substance use before and after the course, (ii) their satisfaction with the course, (iii) factors associated with positive learning and (iv) sociodemographic characteristic, Methodology: Subjects were 3,917 who completed the course and answered both a pre-and port-test questionnaire developed specifically to this end. Results: The sample was subjects were mostly female (60.5%), aged 26-50 years (76%), married / common law couples (55.8%), Caucasian (59.5%), college educated (63.7%), living in Southeast region (51.1%). Participants were mostly from TC (50.7%), graduated on social sciences and humanities (31.7%), with intermediate computer skills (44.9%). At the pre-test measurement, the majority showed a poor knowledge, whereas and the end of the course the majority declared to know much or very much about the course content. Participants with the highest increase (0.05) in knowledge were female (49.58%), less than 30 years (47.6%), single (45.5%), did not work in TC (43.5%), voluntary function (41.2%), working in TC less than a month (51.4%), didn't participate in any continuous education course in substance abuse in the last two years (53.5%), did not usually access e-mail to communicate (57.7%), never used online education environment (57.7%). Students agreed on the applicability to their work of the acquired knowledge (??%), an increased work quality (54.3%), motivation (53.4%) and confidence (49.7%). They considered that the course aims were achieved (58.3%)and there was ...